Introduction: From fetal echocardiography to fetal cardiology: A journey of over half a century. Issue 12 (29th December 2017) - Ge, Shuping; Maulik, Dev
Abstract : In this Special Issue of the Journal, 8 review articles that represent the new developments and applications of fetal echocardiography and fetal cardiology for diagnosis, prognosis, and treatment of fetal cardiovascular disease are included. The goal was to provide an updated review of the evidence for the current and emerging use of fetal echocardiography and cardiac magnetic resonance, improved diagnosis of challenging congenital heart disease, new tools for evaluation of fetal systolic and diastolic function, better prognosis and risk stratification of newborns with congenital heart diseases, and new and promising therapies for fetuses with cardiovascular disease.